Role of Visual Evoked Potential in Direct Traumatic Optic Neuropathy: A Case Report : VEP in Direct TON - Vania, Aurelia; Arimbawa, I Komang; Pratiwi, Ni Made Dwita (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2024)
Traumatic optic neuropathy (TON) is a rare cause of visual impairment following blunt or sharp trauma and the diagnosis is established clinically. Lesions on the optic nerve may not always be visible in neuroimaging examinations. Studies on Visual Evoked Potential (VEP) in TON patients are still limited, despite being beneficial for objectively detecting optic nerve lesions. A 16-year-old male patient was referred to the neurology clinic with a sudden loss of vision in the left eye approximately 25 days after a head injury due to a motor vehicle accident. The patient had epidural bleeding and fractures in the orbital and facial bones, as revealed by a head CT scan. Neurological examination showed a visual acuity of 1/300 in the left eye, left midriasis, and a negative light reflex in the left eye. VEP examination of the left eye revealed prolonged P100 latency and a decrease in P100 amplitude (>50%), indicating a lesion in the left optic nerve. This visual impairment persisted for up to 6 months post-head trauma. TON is a vision-threatening disorder that should be considered in patients with ocular or head trauma and visual impairment. A decrease in amplitude ratio <50% and prolonged P100 latency >140 ms are associated with poor visual function recovery. VEP examination is an objective assessment of visual pathway integrity and serves as one modality for early TON diagnosis and a predictor of visual function prognosis in TON patients. Keywords: diagnostic; prognostic; traumatic optic neuropathy; visual evoked potential